FOSTERING STUDENTS' CRITICAL THINKING SKILLS THROUGH TECHNOLOGY-BASED INTERACTIVE LEARNING IN THE DIGITAL ERA: MENUMBUHKAN KETERAMPILAN BERPIKIR KRITIS MAHASISWA MELALUI PEMBELAJARAN INTERAKTIF BERBASIS TEKNOLOGI DI ERA DIGITAL - Jasiah, Jasiah (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2023)
This study was motivated by the importance of critical thinking skills in the world of education and aimed to investigate the effectiveness of technology-based interactive learning in enhancing students' critical thinking skills. The research method used was quantitative with a quasi-experimental design, involving two groups: an experimental group and a control group. The experimental group implemented technology-based interactive learning, while the control group used conventional learning methods. The results showed that the experimental group achieved a greater increase in critical thinking skills compared to the control group. Factors such as the frequency of technology use in learning, students' ability to use the provided technology features, the appropriateness of technology use for learning needs, students' reactions to the technology used, and the effectiveness of technology use in enhancing students' critical thinking skills all showed significant differences between the two groups. The results show that technology-based interactive learning can improve students' critical thinking skills and learning outcomes more effectively. the use of technology-based interactive learning can be a good alternative in improving the quality of education. Keywords: Critical, Digitization, Interactive, Learning, Technology